Solar power from the desert: A sensible and feasible energy solution? - Isabelle Werenfels; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2009)
The idea of supplying Germany and Europe with solar energy from the desert remains highly controversial, but it is an idea that has been gaining traction with both policy makers and the private sector. This is because of two recently launched, large-scale projects: the Solar Plan of the EU and Southern Mediterranean countries, and the Desertec Industrial Initiative, a solar energy project privately financed by a group of European companies. Despite all the financial, political, and economic uncertainties these projects entail, there is virtually no viable energy alternative. What is required now are clear policies at the German and European level, providing appropriate incentives for the successful implementation of these projects - without which, they will remain just a vision
Keywords: 320